Odpowiedzi

2010-01-14T19:53:39+01:00
-1 1/3 - 2/9+ 1/6= -1 6/18 - 4/18 + 3/18= -1 7/18

1 1/8 - 2 1/4 - (-1/2)= 1 1/8 - 2 2/8 + 4/8 = 1 5/8 - 2 2/8= 13/8 - 18/8 = - 5/8

(-2,1) + 1/3 -3 = -2 1/10 +1/3 -3 = -2 3/30 + 10/30 - 3 = -5 3/30 + 10/30 = -4 27/30
3 5 3
2010-01-14T19:58:01+01:00
A) -1 1/3 - 2/9 + 1/6=
-4/3 - 2/9 + 1/6 =
-12/9 - 2/9 + 1/6=
-24/18 - 4/18 + 3/18=
-25/18=
- 1 i 7/18

b)1 1/8 - 2 1/4 - ( - 1/2)=
9/8 - 9/4 + 1/2=
9/8 - 18/8 + 4/8=
-5/8

c)(-2,1)+ 1/3 - 3=
-21/10 + 1/3 -3=
-63/30 + 10/30 - 3=
-53/30- 3=
-1 i 23/30 - 3=
-4 i 23/30
2 5 2